2021
DOI: 10.24297/jbt.v9i.9109
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Graph-Theoretic Model of Single Point Mutations Associated with Sickle Cell Anemia Disease

Abstract: Many diseases like cystic fibrosis and sickle cell anemia disease (SCD), among others, arise from single point mutations in the respective proteins. How a single point mutation might lead to a global devastating consequence on a protein remains an intellectual mystery. SCD is a genetic blood-related disorder resulting from mutations in the beta chain of the human hemoglobin protein (simply, β-globin), subsequently affecting the entire human body. Higher mortality and morbidity rates have been reported for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Protein conformations are honed by natural selection to optimize biological functions. Many studies have demonstrated in vivo, in situ, and in silico that >90% of missense mutations altering the amino acid sequence are deleterious, chiefly because they tend to perturb normal protein folding [52][53][54]. Moreover, external factors such as environmental stresses (altered temperature or pH, or oxidative damage) can exacerbate this disruption, preventing a protein from attaining a functional or stable structure, subsequently contributing to age-progressive diseases [15,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Protein conformations are honed by natural selection to optimize biological functions. Many studies have demonstrated in vivo, in situ, and in silico that >90% of missense mutations altering the amino acid sequence are deleterious, chiefly because they tend to perturb normal protein folding [52][53][54]. Moreover, external factors such as environmental stresses (altered temperature or pH, or oxidative damage) can exacerbate this disruption, preventing a protein from attaining a functional or stable structure, subsequently contributing to age-progressive diseases [15,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%